Hitchhiking into the future on a fly: Toward a better understanding of phoresy and avian louse evolution (Phthiraptera) by screening bird carcasses for phoretic lice on hippoboscid flies (Diptera). (18th February 2022) - Lee, Leshon; Tan, David J. X.; Oboňa, Jozef; Gustafsson, Daniel R.; Ang, Yuchen; Meier, Rudolf
Abstract: Many phoretic relationships between arthropods are understudied because of taxonomic impediments. We here illustrate for avian lice riding on hippoboscid flies how new natural history data on phoretic relationships can be acquired quickly with modern and cost‐effective barcoding techniques. Most avian lice are host‐specific, but some can arrive on new hosts by hitchhiking on hippoboscid flies that feed on bird blood. Our summary of the literature yielded 254 published records which we here show to belong to two large and 13 small interaction networks for birds, flies, and lice. In order to generate new records, we developed a protocol based on screening bird carcasses sourced with the help of citizen scientists. The inspection of 131 carcasses from Singapore led to the first record of a Guimaraesiella Eichler (Ischnocera: Philopteridae) louse species riding on Ornithoica momiyamai Kishida flies collected from a pitta carcass. Phoresy may explain why this louse species is now known from three phylogenetically disparate hosts ( Pitta moluccensis (Müller), Ficedula zanthopygia (Hay); Pardaliparus elegans Lesson). A second new case of phoresy enhanced a large interaction network dominated by Ornithophila metallica (Schiner), a cosmopolitan and polyphagous hippoboscid fly species. Overall, we argue that many two‐ and three‐way phoretic relationships between arthropods (e.g., mites, pseudoscorpions, beetles, flies) can be resolved with cost‐effective large‐scale NGS barcoding, which can be used to partially overcome taxonomic impediments by pre‐sorting specimens for taxonomic revision. Abstract : Based on 254 published records, we use species interaction networks to illustrate what is known about avian louse hitchhiking on hippoboscid flies. We then propose a protocol for obtaining new records by finding flies carrying lice on bird carcasses followed by species‐level sorting of all flies and lice with cost‐effective NGS barcodes. Screening 131 birds from 54 species sourced with the aid of citizen scientists yielded 32 hippoboscid flies of which three carried new lice and thus revealed new phoresy records. We propose that many two‐ and three‐way phoretic relationships can be resolved via species‐level sorting with large‐scale NGS barcoding, which can quickly yield information on species interaction and prepare the specimens for taxonomic revision.